Towards the built environment linguistics - Wang, Qi (2008)
In the history of the built environments theoretical development, the architecture, city and landscape have all been considered as language. Differing from subjects and scholars, various built environment languages have existed, durably or ephemerally. Some stressed the structure of languages and extracted the built environment dictionaries; some emphasized the linguistic characteristics of language and compiled the built environment grammar. They are all great achievements in built environment theory; however, since the connatural difference between the tangible buildings and the intangible spoken & written languages, this concept - the built environment languages - are still esoteric and intricate for the public.